COMPARISON OF VITAMIN, PEPTIDE AND MALONDIALDEHYDE CONTENT OF DIFFERENT EGGS - Tela, Aminu Haruna; Karatas, Fikret; Saydam, Sinan (My University, 2019)
In this work, vitamin A, E, C, MDA, beta-carotene, lycopene, glutathione and ghrelin levels of local chicken(organic), farm chicken, duck, quail and goose eggs were determined by HPLC. The amount of vitamin Aand E found to be higher in the farm chicken egg than other eggs. ?-carotene and lycopene found to be thehigher (P<0.005) in the organic chicken egg. On the other hand, vitamin C, ghrelin, GSSG and MDA foundto be higher in the quail's egg, but GSH was the higher in goose egg. Vitamin A and GSSG were lowest inthe organic chicken egg while vitamin E was the lowest (P<0.005) in the quail's egg. The amount of vitaminC and ?-carotene and MDA were found to be lowest in goose egg. Also, lycopene and GSH were found tobe lowest in the duck egg, but ghrelin was found lowest (P<0.005) in the farm chicken egg.
Keywords: Kimya; Analitik